That Printer of Udell's: A Story of the Middle West - Wright, Harold Bell, 1872-1944 (Salt Lake City, UT : Project Gutenberg, 2004)
(3z(BThat Printer of Udell's: A Story of the Middle West(3y (Bby Harold Bell Wright is a novel likely written in the early 20th century. The story centers around the struggles and growth of its main character, Dick Falkner, a young man haunted by the tragic past of his family and seeking a fresh start in a bustling mining town. As he navigates the challenges of poverty, personal demons, and societal indifference, the narrative explores themes of redemption, resilience, and the impact of one$1 (Bs upbringing. The opening of the novel presents a powerful contrast between the innocence of Dick as a boy and the grim realities he faces as a young man. Initially, we witness Dick's traumatic childhood, defined by a mother$1 (Bs dying wish and a father$1 (Bs alcoholism, setting the stage for his lifelong battle against the shadows of his past. This backstory leads us to present-day Boyd City, where Dick, now a young adult, is desperate to find work amid a sea of rejection and hardship. His encounters highlight the harsh realities of life for those at the mercy of economic forces, framing Dick's journey not only as one of physical survival but also as a quest for self-identity and purpose amidst the complex fabric of society. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/That_Printer_of_Udell%27s
Release date is 2004-08-01
Produced by Vital Debroey, Charles Aldarondo and the Online Distributed Proofreading Team
Keywords: Young men -- Fiction; Christian fiction; Middle West -- Fiction; Printers -- Fiction